DAMPAK PENDIDIKAN MATEMATIKA REALISTIK INDONESIA TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Sugiman, Sugiman; Kusumah, Yaya S. (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2010)
This quasi-experimental study aims to determine the impact of realistic mathematics education (RME) on increasing Mathematical Problem-Solving Abilities (MPSA). The research design used was the non-equivalent control group with the subject population of all junior high school students in the city of Yogyakarta originating from low (C), moderate (B), and high (A) levels. From each school level, one school was taken then from each school taken an experimental class that received RME and one class of control who received regular learning (PB). The instrument used is in the form of two sets of equivalent MPSA tests. Data analysis uses the t-test and Anava. The results of the research were: (1) an increase in the MPSA of RME students was higher than the increase in the MPSA of PB students for all students and all levels of the school; (2) the highest increase in MPSA for RME students occurs at level A schools; and (3) there is no interaction between learning at school level in increasing MPSA.